Reference Management Software: a Comparative Analysis of Four Products. - Ron Gilmour; Laura Cobus-Kuo (Issues in Science and Technology Librarianship)
Reference management (RM) software is widely used by researchers in the health and natural sciences. Librarians are often called upon to provide support for these products. The present study compares four prominent RMs: CiteULike, RefWorks, Mendeley, and Zotero, in terms of features offered and the accuracy of the bibliographies that they generate. To test importing and data management features, fourteen references from seven bibliographic databases were imported into each RM, using automated features whenever possible. To test citation accuracy, bibliographies of these references were generated in five different styles. The authors found that RefWorks generated the most accurate citations. The other RMs offered contrasting strengths: CiteULike in simplicity and social networking, Zotero in ease of automated importing, and Mendeley in PDF management. Ultimately, the choice of an RM should reflect the user's needs and work habits.